The Exodus-conquest narrative: the composition of the non-priestly narratives in Exodus-Joshua - Germany, Stephen (Forschungen zum Alten Testament, 2017)
"Cover" -- "Preface" -- "Table of Contents" -- "Chapter 1: Introduction" -- "1. Contextualization of the Problem" -- "2. Methodology" -- "Chapter 2: Out of Egypt (Exod 1â12)" -- "1. Pharaohâs Oppression of the Israelites (Exod 1)" -- "1.1. Literary-critical analysis" -- "1.2. Macrocontextual analysis" -- "1.3. Synthesis" -- "2. Mosesâ Birth and Flight from Egypt (Exod 2:1-15abÎ±)" -- "2.1. Literary-critical analysis" -- "2.2. Macrocontextual analysis" -- "2.3. Synthesis" -- "3. Moses in Midian (Exod 2:15bÎ²â4:31)" -- "3.1. Literary-critical analysis" -- "3.2. Macrocontextual analysis" -- "3.3. Synthesis" -- "4. The First Encounter with Pharaoh (Exod 5:1â6:1)" -- "4.1. Literary-critical analysis" -- "4.2. Macrocontextual analysis" -- "4.3. Synthesis" -- "5. A Second Commissioning of Moses (Exod 6:2â7:7)" -- "5.1. Literary-critical analysis" -- "5.2. Macrocontextual analysis" -- "5.3. Synthesis" -- "6. The Plagues and the Departure from Egypt (Exod 7:8â12:51)" -- "6.1. Literary-critical analysis" -- "6.2. Macrocontextual analysis" -- "6.3. Synthesis" -- "7. Result " -- "Chapter 3: Into the Wilderness (Exod 13â18)" -- "1. The Itinerary Notices in Exodus and Numbers" -- "2. The Miracle at the Sea (Exod 13:17â14:31)" -- "2.1. Literary-critical analysis" -- "2.2. Macrocontextual analysis" -- "2.3. Synthesis" -- "3. The Song at the Sea and the Song of Miriam (Exod 15:1-21)" -- "3.1. Literary-critical analysis" -- "3.2. Macrocontextual analysis" -- "3.3. Synthesis" -- "4. Marah and Elim (Exod 15:22-27)" -- "4.1. Literary-critical analysis" -- "4.2. Macrocontextual analysis" -- "4.3. Synthesis" -- "5. Quails and Manna (Exod 16)" -- "5.1. Literary-critical analysis" -- "5.2. Macrocontextual analysis" -- "5.3. Synthesis" -- "6. Water from a Rock (Exod 17:1Î²b-7)" -- "6.1. Literary-critical analysis" -- "6.2. Macrocontextual analysis